1991
DOI: 10.1021/bi00227a013
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic tryptophan fluorescence of Schizosaccharomyces pombe mitochondrial F1-ATPase. A powerful probe for phosphate and nucleotide interactions

Abstract: Mitochondrial F1 from the yeast Schizosaccharomyces pombe, in contrast to the mammalian enzyme, exhibits a characteristic intrinsic tryptophan fluorescence with a maximal excitation at 291 nm and a maximal emission at 332 nm. Low values of Stern-Volmer quenching constants, 4.0 M-1 or 1.8 M-1, respectively, in the presence of either acrylamide or iodide, indicate that tryptophans are mainly buried inside the native enzyme. Upon subunit dissociation and unfolding by 6 M guanidine hydrochloride (Gdn.HCl), the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…As a consequence, the presence of the 6 subunit depends on the presence of the E subunit in a rho-context. This points to an interaction between the two subunits, which was proposed previously for pig heart F, where such a 68 complex was purified from F,-ATPase as a molecular entity (Penin et al, 1990;Divita et al, 1991) and confirmed from overproduced bovine subunits (Orriss et al, 1996).…”
Section: Discussionsupporting
confidence: 73%
“…As a consequence, the presence of the 6 subunit depends on the presence of the E subunit in a rho-context. This points to an interaction between the two subunits, which was proposed previously for pig heart F, where such a 68 complex was purified from F,-ATPase as a molecular entity (Penin et al, 1990;Divita et al, 1991) and confirmed from overproduced bovine subunits (Orriss et al, 1996).…”
Section: Discussionsupporting
confidence: 73%
“…This can thus in principle be expressed (Bukulova-Orlova et al, 1974) as (KQ,protein/KQ,tryptophan) *(qtryptophan/qprotein), where the q values are the quantum yields for the protein and free tryptophan derivatives. In practice, the quenching rate constants for exposed tryptophans in denatured proteins are usually much smaller than for free tryptophan derivatives or small peptides (Ivkova et al, 1971;Eftink & Ghiron, 1976;Divita et al, 1991). Results for spectrin are given in Table 2, from which it can be seen that the tryptophan side-chains are moderately accessible to acrylamide, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the following are literature data for acrylamide quenching constants: N-acetyltryptophanamide, 17.5; glucagon, 10.5; globular proteins, [1][2][3][4][5][6][7][8][9] (Eftink & Ghiron, 1976). The quenching constant for N-acetyltryptophanamide by iodide is 6.0 (Divita et al, 1991); and the quenching constant for tryptophan by caesium ion is 2.1 (Ivkova et al, 1971). Shows upward curvature * Determined from slope of Stern-Volmer plot at the origin.…”
Section: Resultsmentioning
confidence: 99%
“…The potassium iodide stock solution also contained 0.1 mM potassium thiosulfate in order to prevent I 3 Ϫ formation, which would quench tryptophan fluorescence emission (32). A control experiment conducted with similar concentrations of KCl indicated that ionic strength did not significantly modify the fluorescence emission of HprK.…”
mentioning
confidence: 99%